1949
DOI: 10.1104/pp.24.4.753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photoperiod and Nitrogen Supply on Growth and Reproduction in the Gherkin

Abstract: In view of the fragmentary knowledge of and growing interest in the ontogeny of cueurbits, an experiment was undertaken to trace certain metabolic and formative processes during the life cycle of a representative species of this family. Though many species of cucurbits are known to be dayneutral in respect to flowering, their growth and certain aspects of reproduction are, nevertheless, known to be highly responsive to day lenlgth and nitrogen supply (10,11,12,38). Hence, contrasted conditions of day length an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1949
1949
1987
1987

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…These results support the findings reported for both monoecious cucurbits (Dzhaparidze, 1976;Hall, 1949;Heslop-Harrison, 1972;Minina, 1938) as well as other plants such as Cannabis sativa (Tibeau, 1936), Spinacea oleracea (Laurent, 1903), Zea mays (Choudhri & Krishan, 1946;Minina, 1938).…”
Section: Discussionsupporting
confidence: 82%
“…These results support the findings reported for both monoecious cucurbits (Dzhaparidze, 1976;Hall, 1949;Heslop-Harrison, 1972;Minina, 1938) as well as other plants such as Cannabis sativa (Tibeau, 1936), Spinacea oleracea (Laurent, 1903), Zea mays (Choudhri & Krishan, 1946;Minina, 1938).…”
Section: Discussionsupporting
confidence: 82%
“…Thompson (76) working with spinach, Tibeau (77) with hemp, and Sahlnin (64) with corn observed that high levels of nitrogen stimulated the production of pistillate flowers while low nitrogen levels favored stamlnate flower formation. Similar observations have been reported by Tied j ens (78) and Dearborn (18) for cucumbers ( Cucumis sativus ), by Hall (30) for gherkins ( Cucumis anguria ) f by Sabinin (64) and Minina (51) for cucumbers and watermelons, and by Brantley (11) for cantaloupes and watermelons.…”
Section: Effgc^s Qr Qualitysupporting
confidence: 84%
“…The effect of the photoperiod is different on different parts of the plant and under different conditions. Hall (1949) grew gherkins under green-house conditions from seedling to maturity. At high nitrogen levels, plants given a 16-hour day had larger stems than those under 8 hours but at low nitrogen levels this was reversed and plants under the shorter days grew larger.…”
Section: Duration Of Lightmentioning
confidence: 99%